Impacted teeth: Their place is in the dental arch - Alberto Consolaro; Mauricio de Almeida Cardoso (Dental Press Editora, 2020)
ABSTRACT The starting point for the treatment of unerupted teeth should consider the fact that, biologically, the pericoronal follicle maintains the ability to release EGF and other mediators responsible for eruption over time. The eruptive events may be guided and directed, so that teeth may occupy the space prepared to receive them in the dental arch, as showed in the case presented to evidence the following principle to be considered in these cases: "Regardless of the position of an unerupted tooth, it may be biologically directed to its place in the dental arch. The orthodontist should apply a mechanics to guide it and park it at its site."